2017
DOI: 10.1002/erv.2572
|View full text |Cite
|
Sign up to set email alerts
|

Naturalistic Outcome of Family‐Based Inpatient Treatment for Adolescents with Anorexia Nervosa

Abstract: Inpatient family-based therapy for AN may be a promising therapeutic approach for adolescents that fail to respond to outpatient treatment and should be investigated further. Copyright © 2017 John Wiley & Sons, Ltd and Eating Disorders Association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 22 publications
3
34
0
4
Order By: Relevance
“…Anorexia nervosa There were three studies found examining inpatient treatment utilizing a family-based approach, one of which included 37 patients [211], and the other two studies which included one patient each (i.e. case reports) [39,63] (Table 41).…”
Section: Family-based Inpatient Carementioning
confidence: 99%
See 2 more Smart Citations
“…Anorexia nervosa There were three studies found examining inpatient treatment utilizing a family-based approach, one of which included 37 patients [211], and the other two studies which included one patient each (i.e. case reports) [39,63] (Table 41).…”
Section: Family-based Inpatient Carementioning
confidence: 99%
“…case reports) [39,63] (Table 41). Length of stay in hospital was a mean of 20.6 weeks (SD = 13.6, range 3-58) in the first study [211] and 10 days in one case report [39] and unclear in the second case report [63]. Mean weight gain was reported as 7.5 kg in the case series [211], a change in BMI from 16.32 to 17.5 in one case report [39], and a change in BMI of 15.4 to 19.5 in the other case report [63].…”
Section: Family-based Inpatient Carementioning
confidence: 99%
See 1 more Smart Citation
“…The child and adolescent inpatient unit admits patients up to 18 years old, and has beds for a maximum of five patients and their families. Details regarding the adaptation of FBT to an inpatient treatment setting have been described elsewhere [17,18].…”
Section: Setting and Participantsmentioning
confidence: 99%
“…Three studies (total n = 39) examined inpatient treatment utilizing a family-based approach [38][39][40], and three papers (total n = 296) reported on inpatient treatment utilizing a cognitive behavioural (CBT) approach [41][42][43]. In all studies patients gained weight in hospital, although measures by which weight changes were reported varied, as did LOS (Table 1).…”
Section: Resultsmentioning
confidence: 99%